The influence of tax literacy, digital literacy and the implementation of m-tax application on individual taxpayer compliance at KPP Pratama Surabaya Mulyorejo - Ndung, Oktaviana; Methasari, Melanny (International Journal of Applied Finance and Business Studies, 2025)
This study aims to empirically analyze how tax literacy affects individual taxpayer compliance, as well as examine the role of digital literacy as a moderating factor that strengthens the relationship between tax literacy and tax compliance. In addition, this study also explores the impact of the use of the M-Tax application on taxpayer compliance, as well as the simultaneous relationship between tax literacy, digital literacy, and the use of the M-Tax application on the level of compliance. The approach used in this study is quantitative descriptive with multiple linear regression analysis methods to test the effect of independent variables on the dependent variable. This study involved a population of individual taxpayers registered at the KPP Pratama Surabaya Mulyorejo, with a total population of 3,507 people, and a sample of 50 respondents. The results of the study indicate that tax literacy, digital literacy, and the use of the M-Tax application significantly affect the level of taxpayer compliance. Overall, these three variables make a substantial contribution to increasing taxpayer compliance. These findings provide empirical evidence of the importance of tax literacy, digital literacy, and the use of technology applications in supporting tax compliance among individual taxpayers.